Can I Access AI Radiology Reports? Navigating Patient Rights in the Age of Digital Health - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The integration of Artificial Intelligence AI into clinical practice, particularly in radiology, is rapidly transforming healthcare. AI algorithms are now ro...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Clinical Decision Support